Legal research at Ahmad Ibrahim Kulliyyah of Laws International Islamic university Malaysia: trends and policies - Kadaouf, Hunud Abia; Oseni, Umar Aimhanosi; Maidin, Ainul Jaria (International Islamic University Malaysia, 2010)

(untitled)
The primary function of Ahmad Ibrahim Kulliyyah (Faculty) of Laws, at the very beginning of its inception, was that ofteaching civil/aw and Shari'ah subjects. As it matured, its vision has been varied from teaching to that of research with the aim of attaining the status of a full research institution that provides both quality research and best legal education in the region. Similar to other institutions of higher education in Malaysia, the responsibility of research is a shared function of both graduate students and the academic staff. The research output, on the part of the students is mostly composed of either Master Dissertations or PhD Theses. The academic members of the Faculty, however, are involved either in direct research, individually or jointly, supervision, and publications of their findings. By investigating and analyzing factors influencing research activities at AlKOL in the past twenty years, the researchers will be able to identify the general trends and development ofresearch as it unfolded over years. The researchers hope that the policymakers, at both Faculty and University levels, will use the findings to improve research quality by boldly addressing the problems hampering research progress at AIKOL.